Bisexual Lives and Aging in Context: A Cross-National Comparison of the United Kingdom and the United States. (July 2019) - Jen, Sarah; Jones, Rebecca L.
Research on bisexual histories and identities in later life is limited and reflects only single-nation studies. This article compares findings from two independently conducted studies of bisexual aging, in the United Kingdom and the United States, using a discourse analytic and life course perspective. The goals were to compare how participants narrated and made sense of their bisexual experiences in later life and to examine ways in which historical and cultural contexts shaped their accounts. Findings indicate that similar histories around lesbian separatism and the HIV/AIDS epidemic enabled shared discursive resources, while differing ethnic and racial relations enabled distinctive discursive possibilities. In both studies intersectional experiences, particularly including being a person of color and having a transgender history, profoundly affected individual narratives. Future research will benefit from creative conceptualizations of bisexuality, applying the life course perspective in research and practice, and supporting the diverse and resilient ways bisexual older adults use language.